Note on oscillationa theorems for third order non-linear difference equations - Jaffer I., Mohammed Ali; B., Selvaraj (Tamkang Journal of Mathematics, 2012)
In this paper some sufficient conditions for oscillation of all solutions of certain difference equations are obtained. Examples are given to illustrate the results.